A comparison between near-infrared (NIR) and mid-infrared (ATR-FTIR) spectroscopy for the multivariate determination of compositional properties in wheat bran samples. (February 2016) - Hell, Johannes; Prückler, Michael; Danner, Lukas; Henniges, Ute; Apprich, Silvia; Rosenau, Thomas; Kneifel, Wolfgang; Böhmdorfer, Stefan
Abstract: The objective of this study was a comparison of the performance of Fourier transformed near-infrared (NIR) with Fourier transformed mid-infrared (MIR) spectroscopy using attenuated total reflectance for the multivariate determination of compositional parameters in wheat bran samples. These parameters were the contents of water, protein, ash, starch, soluble as well as insoluble dietary fibers, and lipids. Partial least squares (PLS) regression was used to construct a calibration model. NIR was found to perform better for ash, starch and soluble as well as insoluble dietary fiber, while MIR was superior only for protein. The scores for water and fat were about equal. The prediction results for ash, insoluble dietary fiber and fat were good. The analysis of soluble dietary fiber suffered from the inaccuracy of the underlying wet-chemical reference method, which had a negative impact on the calibration. Starch was prone to a large relative error despite a good coefficient of determination. Protein and water gave acceptable relative errors but suboptimal goodness of fit. From the precision achieved with a limited sample set, it can be concluded that infrared spectroscopy is an appropriate method to establish a rapid analysis of wheat bran. In general, NIR seemed to be the superior and more robust method. Highlights: Compositional parameters of wheat bran samples were measured. Near- and mid-infrared spectroscopy calibrations were established and compared. Near-infrared spectroscopy gave more accurate predictions. Near-infrared spectroscopy proved to be more robust a method. Calibration was suitable for a rapid screening process.